Análise do efeito da morfina no crescimento de tumor de Ehrlich em camundongos - Huang, Ana Paula Santana [UNIFESP] (2018)
Background and Objectives: The role of opioids on tumor growth is widely discussed. The effect of morphine on tumor is controversial in the studies. The aim of this study was to analyze whether morphine has a direct influence on tumor growth. Methods: Twenty mice received intraperitoneal inoculation of Ehrlich tumor cells and were divided into two groups. Morphine group received 10 mg/kg, and control group received 0.9% saline solution, once daily for 7 days, by gavage of 10 ml/kg. On the tenth day, 5 animals were sacrificed, and 5 were evaluated for survival in each group. The following were evaluated: survival; abdominal circumference; ascites volume; weight; tumor cells in ascites; lymphocytes in the spleen; cytokines in ascites, serum, lymph nodes and spleen; nitrite in ascites; arginase in ascites; superoxide dismutase (SOD) in ascites. Results: The nitric oxide (NO) level in ascites was higher with morphine treatment. There were no differences in the other parameters. Conclusions: The results of this study show that morphine causes changes in some parameters associated with tumor growth in mice as weight, ascites volume and abdominal circumference, being only NO levels in ascites higher after morphine treatment.